Sorting Through Affirmative Action: Two Field Experiments in Colombia - Marcela Ibanez; Gerhard Riener; Ashok Rai (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
Affirmative action is a subject of intense debate. Supporters point to the increased representation of women and minority groups while critics contend that affirmative action can lead to inefficiencies. In this paper we present results from two field experiments that were designed to test how applicants sort in response to affirmative action rules that favor of women. Our results suggest that the criticism of affirmative action is misplaced. We find that affirmative action does not lead to lower standards in the pool of applicants.
Keywords: 330; Field experiment